MAPK p38 regulates inflammatory gene expression via tristetraprolin: Doing good by stealth. (January 2018) - O'Neil, J.D.; Ammit, A.J.; Clark, A.R.
Highlights: TTP negatively regulates expression of large numbers of inflammatory mediators. A TTP knock-out mouse suffers chronic and severe inflammatory pathology. TTP is multiply phosphorylated. Phosphorylation of serines 52 and 178 is mediated by the MAPK p38-activated kinase MK2. Phosphorylation of TTP at serines 52 and 178 causes its inactivation, and is permissive for expression of TTP-regulated inflammatory mediators. Inflammation is reduced by genetically or pharmaceutically interfering with the phosphorylation of serines 52 and 178. Abstract: Tristetraprolin (TTP) is an RNA-destabilizing protein that exerts profound anti-inflammatory effects by inhibiting the expression of tumour necrosis factor and many other inflammatory mediators. The mitogen-activated protein kinase (MAPK) p38 signaling pathway controls the strength and duration of inflammatory responses by regulating both the expression and function of TTP. The kinase MK2 (MAPK activated kinase 2) is activated by MAPK p38, and in turn phosphorylates TTP at two critical serine residues. One consequence of these phosphorylations is the protection of TTP from proteasome-mediated degradation. Another consequence is the loss of mRNA destabilizing activity. The control of TTP expression and function by the MAPK p38 pathway provides an elegant mechanism for coupling the on and off phases of inflammatory responses, and dictating the precise kinetics of expression of individual inflammatory mediators.